Implementasi Undang-Undang Cipta Kerja Pasca Putusan Mahkamah Konstitusi Nomor 168/PUU-XXI/2023: Penelitian - Cecilia Darmadi; Freddy Harris (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study analyzes the implementation of the Job Creation Law in the employment sector in Indonesia, with an emphasis on employment law policies and efforts to achieve legal certainty in its implementation. The research problem formulation includes: (1) how the Job Creation Law is implemented after the Constitutional Court Decision Number 168/PUU-XXI/2023 from the perspective of implementation and legal protection for related parties; (2) what the obstacles and legal challenges faced in the implementation process, and the legal solutions that can be proposed. The research method applied is normative with a descriptive-qualitative approach, which includes an inventory, interpretation, and evaluation of laws and regulations, legal doctrine, jurisprudence, and related scientific literature, especially Law Number 6 of 2023 concerning Job Creation and the Constitutional Court Decision Number 168/PUU-XXI/2023. Secondary data collection was carried out through literature studies and document analysis, which were then analyzed critically and in depth. The research findings indicate that the implementation of the Job Creation Law in the employment sector requires comprehensive interpretation and evaluation to ensure legal certainty and worker protection. Pasca putusan MK, UU tersebut harus diterapkan secara holistik demi keadilan, kepastian hukum, dan perlindungan dalam hubungan industrial.